Описание самца Euchalcia viridis (Lepidoptera, Noctuidae) - Ключко, З.Ф. (Вестник зоологии, 1983)
Fuchalcia viridis Stgr. male from Armenia by external appearance and genitalic structure is similar to £. phrygige Du, differs by darker grey-yellow-green ground colour of the forewing and by more corrugated external medial stripe. Male genitalia are distinct by the shape of valva: shorter harpa with a wide base, very short clavus, the shape of the fullura inferior and pointed short spine of acdeagus. Female genitalia are distinct by sclerotization and the shape of the antral part of the ductus bursae.